2007
DOI: 10.1021/bi7000467
|View full text |Cite
|
Sign up to set email alerts
|

Substitutions in the N-Glycan Core as Regulators of Biorecognition:  The Case of Core-Fucose and Bisecting GlcNAc Moieties

Abstract: Core fucosylation and the bisecting N-acetylglucosamine residue are prominent natural substitutions of the N-glycan core. To address the issue of whether these two substituents can modulate ligand properties of complex-type biantennary N-glycans, we performed chemoenzymatic synthesis of the respective galactosylated and alpha2,3/6-sialylated N-glycans. Neoglycoproteins were then produced to determine these glycans' reactivities with sugar receptors in solid-phase assays and with tumor cells in vitro as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
70
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 93 publications
(72 citation statements)
references
References 56 publications
(95 reference statements)
1
70
0
1
Order By: Relevance
“…In line with literature data [13,20,31] and our gel filtration analysis of aliquots run in parallel the lectin consistently formed (AB) 2 dimers (A = toxin subunit, B = lectin subunit) under these conditions. This confirms that the dimer structure seen in crystals [13,14] was not due to a crystal packing force.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…In line with literature data [13,20,31] and our gel filtration analysis of aliquots run in parallel the lectin consistently formed (AB) 2 dimers (A = toxin subunit, B = lectin subunit) under these conditions. This confirms that the dimer structure seen in crystals [13,14] was not due to a crystal packing force.…”
Section: Resultssupporting
confidence: 90%
“…Analyses of purity and activity were performed by gel filtration, oneand two-dimensional gel electrophoresis, haemagglutination, solid-phase and cell binding/growth assays [20,[23][24][25]. Prior to SANS measurements, H 2 O of freshly prepared VAA solutions in phosphate buffer (PB; 20 mM, pH 7.2, H 2 O) was exchanged to D 2 O by adding PB in D 2 O (20 mM, pD 7.2), followed by a step using a Millipore centrifugal concentrator with a 10 kDa MW cut-off.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In studies of N ‐glycan‐related compounds, Gabius and co‐workers demonstrated that immobilizing a few N ‐glycans onto 125 I‐labeled bovine serum albumin (BSA) moderately regulated the biodistributions and serum stabilities of the proteins in mice 25, 26, 27, 42. The presence of sialic acid residues in the glycoalbumin stabilized the molecules in serum, consistent with the receptor‐mediated excretion mechanism associated with asialoglycoprotein 43, 44, 45.…”
mentioning
confidence: 86%
“…It has been reported that core fucosylation affects the conformations of N-glycans and modulates glycan-lectin interactions and antibody-Fc receptor recognition (41)(42)(43)(44)(45). Moreover, core fucosylation is associated with cancer progression, suggesting that core-fucosylated N-glycans and glycopeptides could serve as novel biomarkers for cancer diagnosis (46,47).…”
mentioning
confidence: 99%